Multilocus genotyping of giardia duodenalis in Malaysia. Infection, genetics and evolution - Huey, C.S.; Mahdy, M.A.K.; Al-Mekhlafi, H.M.; Nasr, N.A.; Lim, Y.A.L.; Mahmud, R.; Surin, J. (Elsevier, 2013)
Giardia duodenalis is considered the most common intestinal parasite in humans worldwide. In Malaysia, 26 many studies have been conducted on the epidemiology of giardiasis. However, there is a scarcity of 27 information on the genetic diversity and the dynamics of transmission of G. duodenalis. The present study 28 was conducted to identify G. duodenalis assemblages and sub-assemblages based on multilocus analysis 29 of the glutamate dehydrogenase (gdh), beta-giardin (bg) and triose phosphate isomerase (tpi) genes. Fae- 30 cal specimens were collected from 484 Orang Asli children with a mean age of 7 years and examined 31 using light microscopy. Specimens positive for Giardia were subjected to PCR analysis of the three genes 32 and subsequent sequencing in both directions. Sequences were edited and analysed by phylogenetic 33 analysis. G. duodenalis was detected in 17% (84 of 484) of the examined specimens. Among them, 71 were 34 successfully sequenced using at least one locus. Genotyping results showed that 30 (42%) of the isolates 35 Q2 belonged to assemblage A, 32 (45%) belonged to assemblage B, while discordant genotype results were 36 observed in 9 specimens. Mixed infections were detected in 43 specimens using a tpi-based assemblage 37 specific protocol. At the sub-assemblages level, isolates belonged to assemblage A were AII. High nucle- 38 otide variation found in isolates of assemblage B made subtyping difficult to achieve. The finding of 39 assemblage B and the anthroponotic genotype AII implicates human-to-human transmission as the most 40 possible mode of transmission among Malaysian aborigines. The high polymorphism found in isolates of 41 assemblage B warrants a more defining tool to discriminate assemblage B at the sub-assemblage level.